Kolaborasi profesi/tenaga kesehatan dalam manajemen bencana meliputi fase pra bencana, siaga darurat, dan tanggap darurat - Wicaksono, Bimo; Kuncoro, Wahyu; Wardani, Wulan Kusuma (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Multi-stakeholder collaboration and coordination are part of disaster management in general. Through collaboration and coordination, the implementation of disaster management will become more effective and targeted. Collaboration and coordination can be said to be an effort to manage the resources available for use in the disaster management cycle (pre-disaster, during a disaster, and post-disaster). In public health disaster management, the involvement of professionals and health workers is important to ensure that people who are at risk or exposed to the threat of disaster have knowledge regarding factors that can disrupt health (physical and mental) or that people affected by disasters can receive health services and minimise the increase in casualties. In the context of disaster preparedness, collaboration or professional involvement of health workers is needed when preparing disaster contingency plans.Cluster coordination mechanisms can bridge actors involvement in disaster management. Health professional organisations can be involved or take part in this mechanism by considering that the membership of each organisation is an asset or resource that may be needed when a disaster occurs. Increasing the number of volunteers at the community level who have been trained regarding emergency response efforts for physical or mental health conditions can ultimately help ease the tasks of professional health workers in locations affected by disasters.